2011
DOI: 10.1105/tpc.110.079095
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids in the Root Play an Important Role in Regulating the Leaf Ionome inArabidopsis thaliana   

Abstract: Sphingolipid synthesis is initiated by condensation of Ser with palmitoyl-CoA producing 3-ketodihydrosphinganine (3-KDS), which is reduced by a 3-KDS reductase to dihydrosphinganine. Ser palmitoyltransferase is essential for plant viability. Arabidopsis thaliana contains two genes (At3g06060/TSC10A and At5g19200/TSC10B) encoding proteins with significant similarity to the yeast 3-KDS reductase, Tsc10p. Heterologous expression in yeast of either Arabidopsis gene restored 3-KDS reductase activity to the yeast ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 86 publications
1
68
0
1
Order By: Relevance
“…However, no KCS involved in VLCFA elongation for sphingolipid synthesis has been reported yet. The LCB1, SBH1 and SBH2, and TSC10A and TSC10B genes encoding the LCB1 subunit of Ser palmitoyltransferase, sphingolipid base hydroxylase1 and sphingolipid base hydroxylase2, and proteins similar to the yeast 3-KDS reductase, which are involved in the sphingolipid biosynthetic pathway, respectively, have been shown to be expressed in whole plants (Chen et al, 2006(Chen et al, , 2008Chao et al, 2011), suggesting that the Arabidopsis KCSs expressed ubiquitously in various organs and tissues may be involved in VLCFA elongation, which is used for sphingolipid biosynthesis. In this study, we found that ubiquitously expressed KCS9 is involved in the elongation of C22 to C24 VLCFAs, which is required for sphingolipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, no KCS involved in VLCFA elongation for sphingolipid synthesis has been reported yet. The LCB1, SBH1 and SBH2, and TSC10A and TSC10B genes encoding the LCB1 subunit of Ser palmitoyltransferase, sphingolipid base hydroxylase1 and sphingolipid base hydroxylase2, and proteins similar to the yeast 3-KDS reductase, which are involved in the sphingolipid biosynthetic pathway, respectively, have been shown to be expressed in whole plants (Chen et al, 2006(Chen et al, , 2008Chao et al, 2011), suggesting that the Arabidopsis KCSs expressed ubiquitously in various organs and tissues may be involved in VLCFA elongation, which is used for sphingolipid biosynthesis. In this study, we found that ubiquitously expressed KCS9 is involved in the elongation of C22 to C24 VLCFAs, which is required for sphingolipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…They are known to play roles in membrane structure, signal transduction, and programmed cell death (Chen et al, 2009). GlcCer and GIPC lipids are the two major classes of sphingolipids in plants (Chen et al, 2008;Li-Beisson et al, 2010;Chao et al, 2011). In Arabidopsis, the cutin polymer is comprised of DCAs, v-hydroxy FAs, and glycerol monomers, which are embedded with and covered by waxes (Bonaventure et al, 2004;Franke et al, 2005).…”
Section: Acyl Group Diversion From Sphingolipids and Surface Lipids Tmentioning
confidence: 99%
“…Identification of genes encoding sphingolipid biosynthetic proteins has implicated sphingolipids in many important processes including ion transport (Chao et al, 2011), endomembrane trafficking (Markham et al, 2011), programmed cell death (Liang et al, 2003), cold tolerance (Chen et al, 2012), stomatal closure (Coursol et al, 2005), and pollen development (Chen et al, 2006). However, little information is available about the roles of sphingolipid glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in genes encoding subunits of serine palmitoyltransferase are pollen lethal, indicating that sphingolipids are essential in plants (Chen et al, 2006;Kimberlin et al, 2013). 3-Ketosphinganine reductase then converts 3-ketosphinganine to sphinganine (Chao et al, 2011), which can be modified by hydroxylation and unsaturation to create up to nine different LCBs with variations in structure. Free LCBs can be converted to ceramide by ceramide synthases, also known as Lag 1 Homolog (LOH) enzymes, which acylate LCBs with fatty acids.…”
Section: Introductionmentioning
confidence: 99%